Implementation of the Latest RPS Preparation Model and Student Worksheets through Learning Tool Development Workshop Activities - Khairunnisah, Noni Antika; Ahmad, Ahmad; Yuli, Reni Silvia; Rosdiyanti, Evi; Azim, Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The quality of learning in higher education is largely determined by the availability of systematically designed learning tools based on learning outcomes. One of the main tools required for lecturers is the Semester Learning Plan (RPS) and Student Worksheet (LKM), which align with the Outcome-Based Education (OBE) approach and the Independent Learning–Independent Campus (MBKM) policy. However, various obstacles remain in developing RPS and LKM in accordance with these standards, particularly among permanent lecturers at the Lombok Business Academy. This Community Service activity aims to implement the latest RPS development model and LKM development through a learning tool development workshop. The activity implementation method uses a participatory approach through the stages of needs analysis, planning, workshop implementation, mentoring, evaluation, and follow-up. Participants are permanent lecturers at the Lombok Business Academy. Data collection techniques include pre- and post-tests, assessments of RPS and LKM products, and participant satisfaction questionnaires. The results of the activity show a significant increase in lecturers' understanding of OBE-based RPS development and LKM development. Furthermore, all participants successfully produced revised lesson plans (RPS) and student worksheets (LKM) in accordance with current standards. Participants' responses to the implementation of the activity were also very positive, both in terms of materials, methods, and mentoring. This activity had a positive impact on improving lecturer competency and strengthening the quality of learning at the Lombok Business Academy. Thus, this activity proved effective in enhancing lecturers' abilities to develop high-quality learning tools oriented towards student learning outcomes.